Levels of 25-hydroxycholecalciferol in human serum in all ages: seasonal differences (Revista Española de Fisiología, 1987)
The 25-hydroxycholecalciferol (25-HCC) levels have been quantified in 172 normal controls.Three groups were considered: children (0-12 years), younger than 50 year-old adults and older than 50 year-old adults.In order to evaluate the seasonal variations in this metabolite their levels throughout the year were quantified.A negative correlationship was observed between age and 25-HCC levels.Grouping the levels according to maximum and minimum solar irradiation, the children's group showed higher values than the other groups in both seasons, while younger group (under 50 years of age) showed higher levels than the older group only in maximum solar irradiation.The children's and younger people's groups showed significant differences in the 25-HCC levels between the period of maximum and minimum solar irradiation which did not occur in the older group.In our geographic area, age and seasons of the year are factors that may influence 25-HCC levels.Therefore knowledge of these factors is basic for understanding correctly these metabolite levels.